2019
DOI: 10.2147/cmar.s186142
|View full text |Cite
|
Sign up to set email alerts
|

<p>The unique invasiveness of glioblastoma and possible drug targets on extracellular matrix</p>

Abstract: Glioblastoma, or glioblastoma multiforme (GBM), is described as one of the most invasive cancer types. Although GBM is a rare disease, with a global incidence of <10 per 100,000 people, its prognosis is extremely poor. Patient survival without treatment is ~6 months, which can be extended to around 15 months with the standard treatment protocol. Given the propensity of GBM cells to show widespread local invasion, beyond the margins seen through the best current imaging techniques, tumor margins cannot be clear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
83
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(84 citation statements)
references
References 52 publications
1
83
0
Order By: Relevance
“…A high expression of tumour progression‐associated proteins, such as MMP‐9, MMP‐2, uPA, VEGF and Cyclin D1, was associated with poor outcomes in high‐grade glioma . MMP‐9, MMP‐2 and uPA promote tumour cell invasion through the digestion of extracellular matrix (ECM) components . Angiogenesis mediated by VEGF is essential for tumour growth and metastasis .…”
Section: Discussionmentioning
confidence: 99%
“…A high expression of tumour progression‐associated proteins, such as MMP‐9, MMP‐2, uPA, VEGF and Cyclin D1, was associated with poor outcomes in high‐grade glioma . MMP‐9, MMP‐2 and uPA promote tumour cell invasion through the digestion of extracellular matrix (ECM) components . Angiogenesis mediated by VEGF is essential for tumour growth and metastasis .…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it is known that the highly invasive nature of GBM cells is aided by the degradation of the cancer cell extracellular matrix (ECM) via protease secretions. 46 Reduced ECM surrounding GBM cells compared to astrocytes may enhance the uptake of the micelles into GBM cells. In addition to enhanced uptake into the cancer cells, the YAP-TEAD pathway, the primary target of VP, is activated more in cancer cells compared to healthy cells.…”
Section: Vp-induced Cell Death In Patient-derived Glioma and Astrocytmentioning
confidence: 99%
“…Conversely, matrix proteases such as gelatinases or uPA act through both degradation of the brain extracellular matrix and the activation of pro-migratory signalling. 13 We have previously demonstrated that exposure of GBM adherent cell lines or oncospheres to osmotic and hydrostatic or centrifugal pressure induces an increase in GBM invasive potential in vitro. In the present study, we investigated whether caveolae mediate the pro-invasive response to pressure in GBM cells.…”
Section: Introductionmentioning
confidence: 99%
“…Several signalling pathways known to be activated in GBM result in increased protease expression. Conversely, matrix proteases such as gelatinases or uPA act through both degradation of the brain extracellular matrix and the activation of pro‐migratory signalling . We have previously demonstrated that exposure of GBM adherent cell lines or oncospheres to osmotic and hydrostatic or centrifugal pressure induces an increase in GBM invasive potential in vitro.…”
Section: Introductionmentioning
confidence: 99%